Історико-правовий аналіз розвитку законодавства про дисциплінарну відповідальність за часів існування СРСР - Подорожній, А. Ю.; Podorozhnii, A. Yu.; Артем Подорожній (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2019. – № 4. – С. 23-29, 2019)
У статті на основі наукової літератури здійснено історико-правовий аналіз розвитку законодавства про дисциплінарну відповідальність за часів існування СРСР. Доведено, що у період існування СРСР правове регулювання дисциплінарної відповідальності характеризувалось тим, що норми законодавства поширювалися на всі категорії працівників, без виокремлення категорій, роду заняття, напряму трудової діяльності працівників. Наголошено, що у цей історичний період застосовувались жорстокі методи укріплення дисципліни праці, а також жорсткі заходи дисциплінарної відповідальності. Due to the fact that disciplinary responsibility ensures the effective organization of social work and the concerted, purposeful activity of the participants in the manufacturing process, it requires research in order to further improve and reform it. But in order for the rules of labor legislation in the field of disciplinary responsibility to correspond to the level of development of social and market relations in society, it is necessary to make research in its historical and legal aspect, which is necessary in order for the positive experience of the past years to be properly reflected in the legislation of modern Ukraine. The analysis of the history of formation and development of this institute, especially during the existence of the USSR, remains insufficiently studied. It is known that the legislation of the Soviet Union most significantly influenced the development of today regulatory support of this area of public relations. In the article, on the basis of the analysis of scientific literature, a historical and legal analysis of the development of legislation on disciplinary liability in the time of existence of the USSR has been carried out. The author has proved that during the period of existence of the USSR legal regulation of disciplinary liability is characterized by the fact that the rules of the current legislation were extended to all categories of employees, without distinguishing categories, occupation, and the direction of employees’ work. It has been emphasized that during this historical period cruel methods of strengthening the discipline of labor were used, as well as strict measures of disciplinary responsibility. Thus, the Labor Law Codes of 1918 and 1922 reflected state policy in the field of labor relations regulation, where criminal liability was again applied in the form of disciplinary sanctions, while other disciplinary measures were already applied. В статье на основе научной литературы осуществлен историко-правовой анализ развития законодательства о дисциплинарной ответственности во времена существования СССР. Доказано, что в период существования СССР правовое регулирование дисциплинарной ответственности характеризовалось тем, что нормы законодательства распространялись на все категории работников, без выделения категорий, рода занятия, направления трудовой деятельности работников. Отмечено, что в этот исторический период применялись жестокие методы укрепления дисциплины труда, а также жесткие меры дисциплинарной ответственности.
Historical and legal analysis of the development of legislation on disciplinary liability at the time of the existence of the USSR
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Історія. History. История; історико-правовий аналіз; историко-правовой анализ; historical and legal analysis; Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; дисциплінарна відповідальність; дисциплинарная ответственность; disciplinary liability; правове регулювання; правовое регулирование; legal regulation; дисципліна праці; дисциплина труда; labor discipline; законодавство; законодательство; legislation